Pediatric gastroenteropancreatic neuroendocrine tumor: A case report and review of the literature. Issue 37 (September 2019) - Gaiani, Federica; de'Angelis, Nicola; Minelli, Roberta; Kayali, Stefano; Carra, Maria Clotilde; de'Angelis, Gian Luigi
Abstract: Introduction: Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are a heterogeneous group of epithelial neoplasms originating from the diffuse neuroendocrine cell system of the gastrointestinal tract and pancreas. They are very rare, especially in pediatric age, and vary widely in terms of clinical presentation, malignant potential, and prognosis. Patient concerns: A 9 years' old, white female child presented with abdominal pain and diarrhea mixed with bright red blood lasting 2 days followed by hematemesis. Diagnosis: Routine laboratory tests revealed microcytic anemia. Upper endoscopy showed a 20-mm polypoid lesion in the posterior wall of the duodenal bulb. Biopsy specimens were taken and histologic analysis showed a well-differentiated neuroendocrine tumor G1, with a ki-67 index <2%, an expression of chromogranine A (CgA), synaptophysin and somatostatin receptor type 2A (SSTR2A). Endoscopic ultrasound showed a 21-mm hypoechoic, hypervascular lesion involving the mucosal, submucosal, and muscular layers and a 15-mm hypoechoic round periduodenal lymph node. Gallium-68-somatostatin receptor positron emission tomography (PET with Ga-DOTATOC) showed one area of tracer uptake in the duodenum and other one near the duodenum compatible with the primary tumor site and a lymph node respectively. All the tests confirmed the diagnosis of a GEP-NET of the duodenal bulb, with a single lymph-node metastasis. Interventions: The patient underwent an open duodenal wedge resection. Outcomes: The follow-up at 6, 24, and 36 months and then yearly after surgery for a total of 42 months showed no evidence of recurrence. Conclusion: Duodenal neuroendocrine tumors represent 1% to 3% of all GEP-NETs. They are rare in adults and extremely rare in children. Therefore, the diagnostic and therapeutic approach should be multidisciplinary, including laboratory, endoscopic, and specific imaging tests and strictly follows guidelines, to avoid misdiagnosis and inadequate treatments. Although the prognosis is benign in most cases, they can present with metastases. Therefore, a careful follow-up is extremely important.